Post‐polymerization modification of branched polyglycidol with N‐Hydroxy phthalimide to give ratio‐controlled amino‐oxy functionalized species. Issue 17 (29th May 2016) - Beezer, Dain B.; Harth, Eva
ABSTRACT: Ratio‐controlled amino‐oxy functionalized, branched polyglycidols are prepared by a post‐polymerizaton modification using and optimizing the Mitsunobu reaction for this purpose. The hydroxyl side‐groups are functionalized with N ‐hydroxy phthalimide and the hydrazinolysis of this group furnishes a new class of branched polyglycidols with pendant amino‐oxy groups. Reproducible functionalization degrees of 17, 33, 43, and 63% of the hydroxyl groups are obtained via the presented developed methodology. MTT assays demonstrate the biocompatibility of amino‐oxy functionalized materials. With this, the prepared structural motifs are valuable precursors for the synthesis of biomaterials, bioconjugates and hydrogels in which orthogonal strategies are desired. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 2820–2825 Abstract : Amino‐oxy polyglycidol derivatives with a tailored degree of functionalization were prepared as building blocks for the application in biomaterials such as bioconjugates and hydrogels. Utilizing optimized Mitsunobu conditions, functionalization degrees of 17%, 33%, 43%, and 63% of the hydroxyl groups will enable more diverse polymeric networks that lacked so far tools to vary network dimensions by keeping hydrophilic characteristics.